Point Mutations in the FLT3-ITD Region Are Rare but Recurrent Alterations in Adult AML and Associated With Concomitant KMT2A-PTD - Stasik, Sebastian; Kramer, Michael; Zukunft, Sven; Röllig, Christoph; Baldus, Claudia D.; Platzbecker, Uwe; Serve, Hubert; Müller-Tidow, Carsten; Schäfer-Eckart, Kerstin; Kaufmann, Martin; Krause, Stefan; Sauer, Tim; et al. (Frontiers in Oncology, 2022)
FLT3-ITD mutations are common druggable alterations in patients with acute myeloid leukemia (AML) and associated with poor prognosis. Beside typical ITD mutations, point mutations and deletions in the juxtamembrane domain (JMD) have been observed. However, due to the low frequency of these alterations, there is only limited information on molecular and clinical associations. To evaluate the prognostic impact of non-ITD mutations in the FLT3 JMD region, we analyzed a large cohort of 1,539 adult AML patients treated in different protocols of the Study Alliance Leukemia, using Next-Generation Sequencing. Non-ITD point mutations and deletions within the FLT3 JMD were identified with a prevalence of ~1.23% (n=19). Both, FLT3-ITD and non-ITD mutations were associated with a higher rate of NPM1 (42-61%; P<0.001) and DNMT3A mutations (37-43%; P<0.001), as well as an increased percentage of peripheral blood (54-65%) and bone marrow blast cells (74%; P<0.001), compared to FLT3-wildtype patients. Most significantly, AML patients with FLT3 non-ITD mutations had a higher rate of concomitant KMT2A-PTD mutations (37.5%; P<0.001) as compared to FLT3-ITD (7%) or FLT3-wildtype cases (4.5%). In a multivariable analysis, FLT3 non-ITD mutations were not an independent prognostic factor. However, patients with dual FLT3 non-ITD and KMT2A-PTD mutations showed a trend for inferior outcome, which points at a functional interaction in this subset of AML.